Thinking culture and critical thinking dispositions of high school students in Turkish Republic of Northern Cyprus - Çelik İskifoğlu, Tubanur and Çerkez, Yaǧmur and İskifoğlu, Gökhan (Frontiers in Psychology, 2022)
This study aimed to investigate the critical thinking disposition levels of 15-18 age group secondary and high school students in different educational settings in Turkish Republic of Northern Cyprus. Since culture is an inevitable part of thinking, this study becomes significant since there is no study investigating thinking culture of youngsters in North Cyprus. After eliciting necessary permissions from the Ministry of Education and ethical boards, 1130 participants at the age range of 15-18, who were selected by stratified random sampling and who voluntarily accepted to contribute to the study, took place as a targeted audience. Data was collected from six independent areas of North Cyprus. Turkish version of the California Critical Thinking Disposition Inventory was used as the main data collection tool and the data was collected via online MS Teams platform. First, most of the participants scored significantly below than the desired criteria set by the related literature for the specified age group. Second, gender differences were studied, and girls were found to be more inclined to think critically than boys in terms of six facets of critical thinking except for truth seeking. Third, an interesting result regarding to urban rural area distinction was elicited in favor of rural areas, which was contradicted with the related literature, and this result was discussed under cultural realms of Cyprus.The basic premises behind each finding and their causal associations with culture were all elaborated on in a detail in the discussion section.